The Emergence of eSports Nutrition: A Review - Fernando J. Ribeiro; Victor M. Viana; Nuno P. Borges; Vitor H. Teixeira (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2021)
Peak cognitive performance is of paramount importance for the sports and competitive activities that depend on a high level of cognitive performance, such as eSports. The popularity of eSports has increased rapidly in recent years and will probably continue to rise in the forthcoming years. Above all, eSports practitioners require higher levels of cognitive abilities and motor skills for optimal performance and may benefit from adequate body composition and proper nutrition, as happens with more traditional athletes. However, there is a noticeable shortage of scientific knowledge in this area, including in nutritional-related aspects. Therefore, the objective of this non-systematic review is to summarize the nutritional strategies that may enhance health, cognitive performance, decrease reaction time and minimize fatigue. This information may be relevant for eSports competitors and set a base for further investigations, which could ultimately lead to the establishment of nutritional recommendations specific for this competitive population.